(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
Uzbek poet and thinker, Sufi allama, Huvaydo son of Khojamnazar Goybinnazar from Chimyan district of Fergana Valley, has been making a great contribution to the history of literature for three centuries with his unique works in the poetry of XVII-XVIII centuries. The poet’s epics such as "Rohati Dil", "Ibrahim Adham", the legacy of the poet’s lyrics and ghazals in various genres, are studied as masterpieces of poetry and serve as an example for the education of a mature generation. Mystical thoughts and mystical ideas in the thinker’s poetry serve as a great example not only for the Uzbek people, but also for humanity. After national independence, the scope of studying the poet’s works expanded. In his poetry, humanistic thoughts, ideas such as love of the Motherland, initiative, hard work, goodness and humanity are glorified.